1990
DOI: 10.1111/j.1365-2389.1990.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Frost action in clay soils. II. Ice and water location and suction of unfrozen water in clays below 0°C

Abstract: The relation between temperature, unfrozen water content (UWC) and shrinkage of a number of clays, and the distribution of ice and water within the clays, was studied. The clays included sodium and calcium Wyoming bentonites, < 1 pm and 1-2 pm kaolinite and three English subsoil clays. On freezing blocks of these clays (initial size up to approximately 1 cm') over a period of months, they shrank progressively with reduction in temperature studied except for the < I pm and 1-2 pm kaolinites, which ceased shrink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…As the temperature is lowered, the ice phase grows and the particle volume fraction of the clay increases. At a critical breakthrough temperature T B and volume fraction φ B , ice is able to enter the pore space between particles (Brown & Payne 1990;Shanti et al 2006). For kaolinite clay, the ice-entry temperature is T B = −0.77…”
Section: Physico-chemical Properties (A) Freezing-point Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the temperature is lowered, the ice phase grows and the particle volume fraction of the clay increases. At a critical breakthrough temperature T B and volume fraction φ B , ice is able to enter the pore space between particles (Brown & Payne 1990;Shanti et al 2006). For kaolinite clay, the ice-entry temperature is T B = −0.77…”
Section: Physico-chemical Properties (A) Freezing-point Depressionmentioning
confidence: 99%
“…• C (Brown & Payne 1990). As far as we are aware, the ice-entry temperature has not been measured for bentonite, though Brown & Payne (1990) found no pore ice down to at least −8…”
Section: Physico-chemical Properties (A) Freezing-point Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a given temperature the concentration φ of the soil in equilibrium with pure ice is dictated by the T f (φ) curve. Eventually the soil becomes fully consolidated (φ → φ p ) and a critical ice breakthrough temperature T E is reached [7,42]. At this temperature ice enters the pore space between particles, and interstitial freezing proceeds.…”
mentioning
confidence: 99%
“…A combination of factors allow the partially frozen soil to segregate, revealing a new lens of pure ice [26,39]. Remarkably, frost heave experiments on highly compressible laboratory soils such as colloidal silica found that there is no pore ice near the ice lenses [6,7,45,46]. These results confirm early observations of Beskow that in clays and fine silts the soil between ice lenses is soft and unfrozen [5,28], but have yet to be explained theoretically.…”
mentioning
confidence: 99%